Riveting the atomically distributed lithiophilic centers in the CNT-reinforced interfacial layer: an ultrathin, light-weight deposition substrate toward superior Li utilization. Issue 37 (7th September 2021) - Zhao, Ting; Li, Shaowen; Wang, Yanzhi; Wang, Helin; Zhang, Min; Tang, Xiaoyu; Liu, Fu; Du, Dou; Zheng, Haoquan; Ma, Yue
Abstract : Superior Li utilization is realized via an ultrathin, lightweight interfacial layer with atomically riveted lithiophilic Zn and interweaved carbon nanotubes. Abstract : The dynamically unstable interfacial properties and the low Li-utilization degree hinder the practical use of metallic lithium anodes in energy-dense battery construction with limited cation sources (lean electrolyte in the anode-free/anode-less model). Herein, an ultrathin interfacial layer of atomic Zn-doped N-doped carbon was prepared by a stepwise pyrolysis process and is proposed to regulate the reversible metallic plating/stripping process toward Cu foil. The ultrathin (∼2 μm) and lightweight (0.25 mg cm −2 ) carbonaceous interfacial layer contained porous Zn-doped N-doped carbon sheets derived from metal–organic frameworks (MOFs) as a storage unit and interweaved carbon nanotubes (CNTs) as the structural support (denoted as the Zn-NC-CNT interfacial layer). The Zn-NC-CNT interfacial layer could effectively modify the Cu deposition substrate, maximizing the Li-utilization degree in both the symmetric cells and in a 2 mA h full battery prototype when integrated with the commercial NMC-811 (LiNi0.8 Mn0.1 Co0.1 O2 ) cathode. This ultrathin layer interfacial modification strategy provides a feasible routine to construct the quasi-anode-free configuration without excessive Li abuse toward balanced energy/power densities and good cycling endurance.